Evaluasi Kinerja Keuangan Berbasis Arus Kas pada PT Perkebunan Nusantara III - Siti Aisyah Siregar (Journal Research of Economic and Bussiness, 2026)
This study employs a cash flow-based approach to evaluate the financial performance of PT Perkebunan Nusantara III (Persero), thereby providing an overview of the company's financial condition. The research applies a quantitative descriptive method using annual financial statement data for the 2020–2024 period. The analysis was conducted by calculating several cash flow ratios, including the cash interest coverage ratio, current debt coverage ratio, cash flow to net income ratio, capital expenditure ratio, total debt ratio, and cash flow adequacy ratio. The results indicate that the company has a relatively good capacity to meet interest obligations, maintain earnings quality, and finance investment activities through internal funding sources. However, the company's ability to settle short-term liabilities, total liabilities, and long-term financing needs remains relatively low. These findings suggest that the company needs to improve the management of cash flows generated from operating activities and strengthen its financial structure. Such efforts are essential to support sustainable improvements in the company's liquidity and solvency in the future. Keywords: Performance Evaluation, Financial Performance, Cash Flow, Cash Flow Ratios